Folic acid conjugated and Ag-carrying organoclay nanoparticles and their response to L929 fibroblast and DLD-1 cancer cells. (2nd January 2017) - Rzayev, Zakir M. O.; Khalilova, Sevda; Salimi, Kouroush
Abstract: This work presents the synthesis and characterisation of intercalated nanocomposites (NCs) from dispersed water solution blends of octadecyl amine-montmorillonite (ODA-MMT) (NC-0), folic acid (FA) conjugated ODA-MMT (NC-1) and Ag-MMT clay as a stable silver carrying agent (NC-2). The composition, chemical/physical and morphology of NCs with in situ intercalating nanostructures were investigated. Effect of organoclay, FA and Ag-MMT on L929 fibroblast (control), human colon carcinoma (DLD-1) cell lines, and the cytotoxicity, apoptosis and necrosis degree were estimated via WST-1/hemocytometric, double staining (as a ribonuclease A enzyme based method) and fluorescence microscopy methods in a dose-dependent manner. The mentioned cell lines integrated with NCs resulted in remarkable change in both morphology and nuclei of DLD-1 and fibroblast cells by apoptosis analysis. The number of necrotic cells were remarkably increased, as the toxic effects of nanocomposite nanoparticles were applied to both cell lines. Finally, the molecular mechanism of anticancer action of functionalised organoclays was elucidated.